PEMBERDAYAAN PEREMPUAN NELAYAN DALAM PENGEMBANGAN USAHA NUGGET KERANG DESA BLURU KIDUL KECAMATAN SIDOARJO KABUPATEN SIDOARJO - Tukiman, Tukiman; Rosida, Rosida; Andarini, Sonja (Department of Public Administration, Universitas Negeri Surabaya, 2018)
Community service is done by the empowerment of women fishermen by developing shell nugget in Bluru Kidul Village, Sidoarjo Sub-district, Sidoarjo Regency. This activity was conducted from March to June 2018, the methods of community service are training, mentoring, and practice of making shell nugget according to the receipe of dough that flavor and hygiene, marketing management practices of packaging and labeling. It aims to create an independent and creative society in projecting their future, the family of fishermen in Bluru Kidul Village, Sidoarjo Sub-District, Sidoarjo Regency, so that they will no longer rely on local government in developing home industry business in their village. In addition, they will be able to stand on their own with potential in their area. Management system based on independence and creativity in the development of shell nugget production is still rare. Therefore, Bluru Kidul Village is expected to be a pilot village especially in the production of shell nugget in East Java in particular, and in Indonesia in general, especially for coastal villages.